An ab initio study of Cu-based delafossites as an alternative to nickel oxide in photocathodes: effects of Mg-doping and surface electronic features. Issue 20 (11th May 2018) - Schiavo, Eduardo; Latouche, Camille; Barone, Vincenzo; Crescenzi, Orlando; Muñoz-García, Ana B.; Pavone, Michele
Abstract : Mg-doped Cu-based delafossite oxides are investigated: the effects of dopants and surface features highlight CuGaO2 as a promising alternative to NiO in p-DSSC. Abstract : CuMO2 delafossites (M = Al, Ga, and Cr) are p-type semiconductor oxides that have been recently proposed as the electrode in p-type dye-sensitized solar cells (p-DSSC) which is an alternative to the standard, low-performing nickel oxide. To assess this potential application of delafossites, we report here a DFT-based investigation of the structural and electronic properties of CuAlO2, CuGaO2 and CuCrO2 . In particular, we address the role of Mg doping to obtain the p-type semiconducting character: the substitution of an M 3+ cation with Mg 2+ is easier with Ga than with Al and Cr, and, in all cases, the hole introduced by Mg 2+ leads to the formation of Cu 2+ species. Moreover, we address surface electronic features in order to characterize the most exposed delafossite surface termination and, more importantly, to predict the valence band maximum energy value, which determines the p-DSSC open circuit potential. From analysis of all our results, CuGaO2 emerges as the most promising system that can boost the development of new photocathodes for p-DSSCs.